Aceptación de algunos materiales de frijol a nivel de finca en el oriente de Antioquia - Herpen, T.C. van; Gallego, C. (International Center for Tropical Agriculture, 1985)
In October 1985, 16 farmers of Carmen de Viboral, located in eastern Antioquia, Colombia, were interviewed for their crop preferences and willingness to change bean variety. The variety Cargamanto was the most preferred because of its high yield, better market share, and higher price compared with other varieties, even though it is slightly susceptible to diseases and the available seed is continually deteriorating. Beans have traditionally been planted in relay cropping with maize, but a tendency exists to plant in monoculture. Farmers are willing to change their traditional variety if new varieties yield more and guarantee a better market price than the variety Cargamanto. `Frijolica LS-3.3` is a variety that is readily accepted by consumers, and has characteristics similar to the variety Cargamanto. However, its market price is slightly lower. Other promising varieties grown in the region are V 5781-34-32-34 and V 7423-225-23-S4